DISKURSUS ISLAM KONTEMPORER - Yusdani Yusdani; M. Roem Syibli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
The research below tries to investigate the trend of Islamic discourse and writing structure of bulletins published every Friday in Yogyakarta Special Territory. The research constitutes descriptive and survey methods based on religiousity and sociological approaches. The data are obtained from six different bulletins namely al-Ikhtilaf al-Rasikh, al-I’tishom, al-Ikhlas, at-Tauhid, and Risalah Jumat. The result revealed that the bulletins distributed in Yogyakarta are generally categorized as substantive either in its paragraph, content, closing paragraph or in their Islamicity discourse.